A glimpse into relapsed refractory multiple myeloma treatment in real-world practice in Spain: the GeminiS study. Issue 1 (31st December 2023) - Ríos-Tamayo, Rafael; Soler, Juan Alfons; García-Sánchez, Ricarda; Pérez Persona, Ernesto; Arnao, Mario; García-Guiñón, Antoni; Domingo, Abel; González-Pardo, Miriam; de la Rubia, Javier; Mateos, María Victoria; ,
ABSTRACT: Objectives: To describe the incorporation of monoclonal antibodies (mAb) in real-world (RW) practice for the treatment of patients with relapsed refractory multiple myeloma (RRMM) in a setting with other treatment alternatives. Methods: This was an observational, multicenter, ambispective study of RRMM treated with or without a mAb. Results: A total of 171 patients were included. For the group treated without mAb, the median (95% CI) progression-free survival (PFS) to relapse was 22.4 (17.8-27.0) months; partial response or better (≥PR) and complete response or better (≥CR) was observed in 74.1% and 24.1% of patients, respectively; and median time to first response in first relapse was 2.0 months and in second relapse was 2.5 months. For the group of patients treated with mAb in first or second relapse, the median PFS was 20.9 (95% CI, could not be evaluated) months; the ≥ PR and ≥ CR rates were 76, 2% and 28.6%, respectively; and the median time to first response in first relapse was 1.2 month and in second relapse was 1.0 months. The safety profiles for the combinations were consistent with those expected. Conclusions: The incorporation of mAb in RW practice for the treatment of RRMM has shown good quality and speed of response with a similar safety profile shown in randomized clinical trials.